Security sage's guide to hardening the network infrastructure - Andres, Steven (Rockland, MA : Syngress Pub., 2004)
Security Sage's Guide to Hardening the Network Infrastructure focuses on both perimeter and internal networks, giving IT and security administrators a complete picture of how they should design and protect their enterprises. Other books may concentrate on perimeter security or host configuration yet ignore the infrastructure connecting the two. While others tend to focus on theory and basic security background, this publication will dive right into the content and help provide real solutions to common IT security problems.
Cover; Contents; Foreword; Defining Perimeter and Internal Segments; Assessing Your Current Networks; Selecting the Correct Firewall; Firewall Manipulation: Attacks and Defenses; Routing Devices and Protocols; Secure Network Management; Network Switching; Defending Routers and Switches; Implementing Intrusion Detection Systems; Perimeter Network Design; Internal Network Design; Index; Related Titles
Title from e-book title screen (viewed Apr. 20, 2004).
Keywords: Computer networks -- Security measures; Electronic books